Unauthorized Banking Transactions as a Manifestation of Cybercrime - Staszczyk, Mateusz (Journal of Finance and Financial Law, 2015)
The development is intended to indicate to one of the key challenges that the banking industry is facing growing cases of bank frauds. Race for supremacy in a comfortable sales – on-line – it becomes an opportunity for criminals to fraud. This means that banks and other financial institutions have in front of you to manage the conflict between its client sales and maintaining its security so that the „convenience” did not become an opportunity for criminals. Hence it is important that the effectiveness of the management of this conflict was perceived by the market regulator.